The Politics and Poetics of Authenticity A Cultural Genealogy of Sinhala Nationalism - Rambukwella, Harshana (UCL Press, 2018)
What is the role of cultural authenticity in the making of nations? Much scholarly and popular commentary on nationalism dismisses authenticity as a romantic fantasy or, worse, a deliberately constructed mythology used for political manipulation. The Politics and Poetics of Authenticity places authenticity at the heart of Sinhala nationalism in late nineteenth and twentieth-century Sri Lanka. It argues that the passion for the 'real' or the 'authentic' has played a significant role in shaping nationalist thinking and argues for an empathetic yet critical engagement with the idea of authenticity.